Modulation of the Inflammasome Signaling Pathway by Enteropathogenic and Enterohemorrhagic Escherichia coli - Yen, Hilo; Karino, Masaki; Tobe, Toru (Frontiers in Cellular and Infection Microbiology, 2016)
Innate immunity is an essential component in the protection of a host against pathogens. Enteropathogenic and enterohemorrhagic Escherichia coli (EPEC and EHEC, respectively) are known to modulate the innate immune responses of infected cells. The interference is dependent on their type III secretion system (T3SS) and T3SS-dependent effector proteins. Furthermore, these cytosolically injected effectors have been demonstrated to engage multiple immune signaling pathways, including the IFN/STAT, MAPK, NF-κB, and inflammasome pathways. In this review, recent work describing the interaction between EPEC/EHEC and the inflammasome pathway will be discussed.